Kebijakan Luar Negeri Arab Saudi Terkait Perempuan dalam Kerangka Visi 2030 - Aliffitria, Bhilla (Jurnal ICMES, 2023)
Saudi Vision 2030 changes domestic policy and Saudi Arabia's foreign policy landscape. Saudi Arabia is trying to change its position on the international stage by involving more women's contributions. This research aims to explain Saudi Arabia's foreign policy regarding women within the framework of Vision 2030. This research used qualitative methods with secondary data from various literature sources, such as books, journal articles, and official documents. The data was analyzed using James N. Rosenau's foreign policy concept, consisting of orientations, commitments or action plans, and forms of behaviour. This research finds that Saudi Arabia's exposure within the Vision 2030 framework is as a tourist destination, financial and commercial centre, as well as a trade centre for a leading exporter of clean energy by including women’s involement. Commitment or action plans are demonstrated through the ambitious master plan contained in Vision 2030. Some forms of behaviour are presented, including cooperation with Sweden regarding the SHE-Leads Program and cooperation with Korea regarding the involvement of Korean companies in Biban.